Strategi Penanganan Permasalahan Sampah Di Kota Kupang - Adri Adri; Jeny J. Therik (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the waste management strategy of the Kupang City Environment and Sanitation Agency in addressing the challenge of increasing waste volume. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation with key informants such as field officers, agency staff, and the community. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing, with validation through source and technique triangulation. The results indicate that the waste management strategy focuses on five main pillars: regulatory strengthening, communication, information, and education (IEC), institutional strengthening, coordination and collaboration, and a circular economy. Despite the strategy's implementation, the target of reducing waste by 1–5% per year has not been achieved, with daily waste volume increasing from 233 tons (2023) to 234 tons (2024). Key obstacles include limited infrastructure, low community participation (approximately 20%), a minimal operational budget, and reliance on landfills. This strategy has been implemented in a structured manner through a clear division of tasks and effective vertical-horizontal communication. Officers demonstrated high commitment, although individual discipline issues persisted. Quarterly evaluations indicated the need to revise the strategy to be more adaptive, data-driven, and technology-driven. Facility improvements, ongoing education, and community engagement are key factors in creating an effective and sustainable waste management system in Kupang City